Structural Basis of Disease-Causing Mutations in Hepatocyte Nuclear Factor 1β, - Lu, Peng (2007)
HNF1β is an atypical POU transcription factor that participates in a hierarchical network of transcription factors controlling the development and proper function of vital organs such as liver, pancreas, and kidney. Many inheritable mutations on HNF1β are the monogenic causes of diabetes and several kidney diseases. To elucidate the molecular mechanism of its function and the structural basis of mutations, we have determined the crystal structure of human HNF1β DNA binding domain in complex with a high-affinity promoter. Disease-causing mutations have been mapped to our structure, and their predicted effects have been tested by a set of biochemical/ functional studies. These findings together with earlier findings with a homologous protein HNF1α, help us to understand the structural basis of promoter recognition by these atypical POU transcription factors and the site-specific functional disruption by disease-causing mutations.